Penolakan Return Barang oleh Pelaku Usaha E-commerce (Analisis Undang Undang Nomor 8 Tahun 1999) Tentang Perlindungan Konsumen - Munawarah, Nizmi; Iqbal, Muhammad; Fithria, Nurul (Media Hukum Indonesia (MHI), 2025)
This study identifies instances of breach of contract (wanprestasi), where goods received by consumers do not match the order or arrive in a damaged condition. Furthermore, the consumer complaint process often becomes difficult and does not receive an adequate response from business actors or the platform itself. Based on initial observations of consumer experiences in Banda Aceh, it was found that return rejections often occur even though consumers have fulfilled the required procedures, such as providing an unboxing video. This reflects a gap between existing regulations and their implementation in practice, which ultimately causes harm to consumers. This study applies a normative juridical method, using an analytical approach to various relevant laws and regulations, including Law Number 8 of 1999 concerning Consumer Protection, Government Regulation Number 80 of 2019 concerning Electronic Commerce, and the Indonesian Civil Code. Primary and secondary data, including interviews with consumers who have experienced return rejections, were collected to gain a comprehensive understanding of the legal position of return rejection by e-commerce business actors and the effectiveness of legal protection for consumers. The purpose of this study is to analyze the legal standing of return rejection by e-commerce businesses and to assess the extent to which Law Number 8 of 1999 can provide effective legal protection for consumers in dealing with such practices. This research is expected to contribute to formulating concrete solutions to the issue of return rejection on the Shopee platform and to optimizing the protection of consumer rights in the digital era based on Law Number 8 of 1999.